Analysis of the Potential of North Bengkulu's Air Nokan River in the Context of Fulfilling Water Needs for Micro-hydro Power Plants and Irrigation - GUSTA GUNAWAN - (Engineering Forum of Western Indonesian Government Universities Board (Forum Teknik, BKS-PTN Wilayah Barat) Indonesia, 2023)
The Air Nokan River is located in Kemumu Village, Arma Jaya District, North Bengkulu Regency which is thought to have potential for agricultural water resources and Micro Hydro Power Plants (PLTMH).The detailed objectives of this study are as follows: i). Calculating how much water is available in the Air Nokan river. ii). Calculating the water requirement for an irrigation area. iii). Calculating the need for water for power generation and iv). Designing buildings for PLTMH. The method of this study is to use various mathematical equations that have been found by previous researchers. The primary data used are river dimensions and flow velocity. The water discharge in the river is calculated using the continuity equation. The mainstay discharge is calculated using the Mock method. Secondary data in the form of rainfall was obtained from three rain measuring stations. Rainfall data is processed using the algebraic average method. Climatological data were obtained from BMKG Bengkulu Province. Evapotranspiration was calculated using the modified Penman method. The results of data processing obtained a cross-sectional area of ??the river 58 m2 and a flow velocity of 1.5 m/s so that the river water discharge is 69.6 m3/s. The maximum discharge required for irrigation purposes is 2.13 m3/s. The maximum discharge required for power generation is 5.5 m3/s. The mainstay discharge with the lowest 85% probability in January is 7.63 m3/s.Based on the results of the analysis, it was concluded that the Air Nokan river can meet the needs of water to flow irrigation canals and power plants